Perspectives of Local Community Leaders, Health Care Workers, Volunteers, Policy Makers and Academia on Climate Change Related Health Risks in Mukuru Informal Settlement in Nairobi, Kenya—A Qualitative Study - Johanne Greibe Andersen (MDPI AG, 2021)
Sub-Saharan Africa has been identified as one of the most vulnerable regions to climate change. The objective of this study was to explore knowledge and perspectives on climate change and health-related issues, with a particular focus on non-communicable diseases, in the informal settlement (urban slum) of Mukuru in Nairobi, Kenya. Three focus group discussions and five in-depth interviews were conducted with total of 28 participants representing local community leaders, health care workers, volunteers, policy makers and academia. Data were collected using semi-structured interview guides and analyzed using grounded theory. Seven main themes emerged: climate change related diseases, nutrition and access to clean water, environmental risk factors, urban planning and public infrastructure, economic risk factors, vulnerable groups, and adaptation strategies. All participants were conscious of a link between climate change and health. This is the first qualitative study on climate change and health in an informal settlement in Africa. The study provides important information on perceived health risks, risk factors and adaptation strategies related to climate change. This can inform policy making, urban planning and health care, and guide future research. One important strategy to adapt to climate change-associated health risks is to provide training of local communities, thus ensuring adaptation strategies and climate change advocacy.